Shifting proximities. Visualizing changes in the maritime connectivity of African countries (2006/2016) - (:unkn) unknown (My University, 2022)
As a process, containerization in Africa is still on-going. In the last decades, a number of new port projects have emerged in parallel with the reorganization of services by shipping companies. To reflect these changes, this paper studies several questions on the geographic differentiation of maritime connectivities across the continent as well as on the longitudinal trends in maritime connectivities in relation to evolving economic, trade and logistical contexts. To this end, we propose a synthetic visualization of the country-level containerized links using the Liner Shipping Bilateral Connectivity Indicator (LSBCI). The resulting graph, obtained through Multidimensional Scaling (MDS), shows that West Africa and East Africa appear as relatively separated subsystems, mediated by several countries in the Northern and the Southern parts of Africa. Between 2006 and 2016, West Africa, initially tied to Europe and America, is increasingly tied to Asia. Our results show major improvements in the maritime connectivity of Morocco, Djibouti and several West African ports. Conversely, most of mainland East African countries stagnate or decline. Connectivities have not converged across the continent. In some cases changes in maritime connectivity mostly result from variations in vessel size. We explore a method to identify these situations.
Keywords: African Research